2021
DOI: 10.3390/brainsci11111412
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Blooded and on Purpose: A Review of the Biology of Proactive Aggression

Abstract: Proactive aggression (PA) is a planned and unprovoked form of aggression that is most often enacted for personal gain or in anticipation of a reward. Frequently described as “cold-blooded” or goal oriented, PA is thought to be associated with low autonomic arousal. With this view in mind, we performed a scoping review of the biological correlates of PA and identified 74 relevant articles. Physiological findings indicated a robust association between PA and reduced resting heart rate, and to a lesser extent a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 239 publications
(328 reference statements)
0
11
0
Order By: Relevance
“…Individuals with low enzymatic activity genotypes (CT and TT) are expected to display high levels of DA in the synapse [ 31 ]. High levels of DA in the synapse can activate dopaminergic receptors, such as DRD1 and DRD2 involved in aggressive behaviour, impulsivity and attention [ 5 , 6 , 7 , 8 ]. Functional DBH rs1611115 was previously reported to be associated with impulsive personality styles but not with affective disorders [ 32 ], suggesting a strong involvement of meso-cortical dopaminergic pathways in this personality trait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with low enzymatic activity genotypes (CT and TT) are expected to display high levels of DA in the synapse [ 31 ]. High levels of DA in the synapse can activate dopaminergic receptors, such as DRD1 and DRD2 involved in aggressive behaviour, impulsivity and attention [ 5 , 6 , 7 , 8 ]. Functional DBH rs1611115 was previously reported to be associated with impulsive personality styles but not with affective disorders [ 32 ], suggesting a strong involvement of meso-cortical dopaminergic pathways in this personality trait.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, there has been an increased focus on the importance of diet on cognitive ability and behaviour, including aggressive behaviour, impulsivity and attention disorders [ 1 , 2 , 3 , 4 ]. It has been suggested that dysfunction in dopaminergic signalling pathways may underlie the development of many of these disorders [ 5 , 6 , 7 ]. In studies on both adults and children, dopamine (DA) hyperactivity in brain regions linked to reward-related motivation (such as the limbic system and prefrontal cortex) has been associated with increases in impulsive and aggressive behaviours [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further contributions to understanding pathological aggression was provided by studies concentrating on the neurobiological correlates of reactive and proactive aggression in overly aggressive groups. In their literature review, Belfry and Kolla presented key results on the biological correlates of proactive aggression, pointing to a blunted sympathetic functioning and, in addition to the amygdala, the involvement of the default mode network [4]. Such blunted physiological arousal was absent in an experimental study conducted by Harmsel and colleagues in a group of delinquent adults and controls [5].…”
Section: Introductionmentioning
confidence: 99%
“…These two questions appear crucial in a world where over 20 million Disability-Adjusted Life Years are lost each year due to interpersonal violence, which ranks it the 18th on the list of the World Health Organization, ahead of many serious diseases including various forms of cancer (World Health Organization communication etc. (Raine and Yang, 2006;New et al, 2007;Belfry and Kolla, 2021). While the utility of sociological, psychological, and criminological approaches is unquestionable, it is widely believed that understanding the biological control of violence may lead to the development of better pharmacological and other tools of control (e.g., deep brain stimulation, Meyer et al, 2016Rizzi et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, criminal violence is associated with a series of neural dysfunctions ranging from prefrontal deficits to amygdala dysfunctions and deficient prefrontal cortex-amygdala communication etc. ( Raine and Yang, 2006 ; New et al, 2007 ; Belfry and Kolla, 2021 ). While the utility of sociological, psychological, and criminological approaches is unquestionable, it is widely believed that understanding the biological control of violence may lead to the development of better pharmacological and other tools of control (e.g., deep brain stimulation, Meyer et al, 2016 Rizzi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%